2011
DOI: 10.1007/s00296-010-1716-7
|View full text |Cite
|
Sign up to set email alerts
|

Moderate loading of the human osteoarthritic knee joint leads to lowering of intraarticular cartilage oligomeric matrix protein

Abstract: The non-pharmacological treatment of osteoarthritis (OA) includes exercise therapy; however, little is known about the specific effect of exercise on the joint per se. The purpose of the present study was to investigate the direct effects of a load-bearing exercise upon cartilage in a single, human osteoarthritic joint determined by biochemical markers of cartilage turnover and inflammation in the synovial fluid (SF), serum and urine. Eleven subjects with OA of the knee(s), but with no other joint- or inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Levels were analyzed in the SF, serum, and urine after 30 minutes of exercise. A significant decrease in COMP concentration was observed in the SF following exercise, whereas aggrecan, CTX‐II, and IL‐6 remained unchanged compared to baseline . No differences in any of the markers were observed in serum or urine between baseline and post‐exercise.…”
Section: The Effects Of Exercise On Cartilage Bio‐composition In Humansmentioning
confidence: 75%
See 1 more Smart Citation
“…Levels were analyzed in the SF, serum, and urine after 30 minutes of exercise. A significant decrease in COMP concentration was observed in the SF following exercise, whereas aggrecan, CTX‐II, and IL‐6 remained unchanged compared to baseline . No differences in any of the markers were observed in serum or urine between baseline and post‐exercise.…”
Section: The Effects Of Exercise On Cartilage Bio‐composition In Humansmentioning
confidence: 75%
“…No differences in any of the markers were observed in serum or urine between baseline and post‐exercise. Based on this study, short term exercise probably induced movement facilitated transport of large COMP molecules from the intra‐articular space through the synovial membrane . It has been suggested that changes in COMP concentration within SF were not sufficient to result in any change at the whole body level.…”
Section: The Effects Of Exercise On Cartilage Bio‐composition In Humansmentioning
confidence: 99%
“…COMP synthesis and release by chondrocytes is mechanically regulated (Piscoya et al, 2005; Wong et al, 1999) and has been shown to be elevated following canine meniscectomy, with peaks around 4 – 8 weeks after injury (Lindhorst et al, 2000). Previous studies have shown that 30 minutes of one-legged knee extension exercise decreases synovial fluid COMP in osteoarthritic knees (Helmark et al, 2012). Furthermore, the knee state and type of exercise impact alterations in COMP levels, as in healthy knees serum COMP levels correlate with cartilage volume changes after drop landing but not after running (Niehoff et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, biomarkers from proteins in serum and synovium have recently been used to study changes in the knee osteoarthritis disease process. Furthermore, some recent studies have reported the effect of exercise interventions on circulating cartilage markers [26,27]. Exercises have shown to cause rise in circulating cartilage markers like cartilage oligomeric matrix protein (COMP), aggrecan and C-terminal telopeptides of collagen type II (CTX-II) [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some recent studies have reported the effect of exercise interventions on circulating cartilage markers [26,27]. Exercises have shown to cause rise in circulating cartilage markers like cartilage oligomeric matrix protein (COMP), aggrecan and C-terminal telopeptides of collagen type II (CTX-II) [27,28]. Additionally, exercises have shown to increase the production of the anti-inflammatory mediator interleukin-10 [29].…”
Section: Introductionmentioning
confidence: 99%